2009
DOI: 10.1614/wt-09-012.1
|View full text |Cite
|
Sign up to set email alerts
|

Problem Weed Control in Glyphosate-Resistant Soybean with Glyphosate Tank Mixes and Soil-Applied Herbicides

Abstract: Although glyphosate controls many plant species, certain broadleaf weeds in Nebraska's cropping systems exhibit various levels of tolerance to the labeled rates of this herbicide, including ivyleaf morningglory, Venice mallow, yellow sweetclover, common lambsquarters, velvetleaf, kochia, Russian thistle, and field bindweed. Therefore, two field studies were conducted in 2004 and 2005 at Concord and North Platte, NE, to evaluate performance of (1) seven preemergence (PRE) herbicides and (2) glyphosate tank mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 21 publications
2
30
0
1
Order By: Relevance
“…Although the regression lines appear similar at some locations (e.g. at Surduk in 2008and 2009, Zemun Polje in 2008and Radmilovac in 2009, the lines are different from each other based on the regression parameters (Figure 1a, b; Table 2). In general, sunflower yields varied between years and among locations.…”
Section: Critical Time For Weed Removalmentioning
confidence: 92%
See 1 more Smart Citation
“…Although the regression lines appear similar at some locations (e.g. at Surduk in 2008and 2009, Zemun Polje in 2008and Radmilovac in 2009, the lines are different from each other based on the regression parameters (Figure 1a, b; Table 2). In general, sunflower yields varied between years and among locations.…”
Section: Critical Time For Weed Removalmentioning
confidence: 92%
“…Even though the use of HRCs may have advantages over conventional herbicide programmes, there are risks associated with their use which include herbicide drift, misapplication, weed resistance, weed population shifts and HRC volunteer plants in subsequent crops (Sikkema et al 1999;Knezevic et al 2003Knezevic et al , 2009). The cropping systems utilizing HRCs need to include the fundamental components of integrated weed management (IWM) systems such as knowledge of the critical period for weed control (CPWC) (Van Acker et al 1993;Knezevic et al 2002Knezevic et al , 2003, which can provide guidelines for a well-timed use of low-or non-residual POST herbicides (Knezevic et al 2002(Knezevic et al , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed the effective broad‐spectrum weed control when premixes from Group 2 (ALS‐inhibitors), Group 5 (Photosystem II [PSII]‐inhibitors), Group 14 (protoporphyrinogen oxidase [PPO]‐inhibitors), and Group 15 (long‐chain fatty acid‐inhibitors) herbicides. Similarly, others reported that PRE application of PPO herbicides tank‐mixed with ALS‐inhibiting herbicides provided an effective control of broadleaf species (Belfry et al, 2015; Walsh et al, 2015); including kochia, Russian thistle ( Salsola tragus ), field bindweed ( Convolvulus arvensis ), velvetleaf, common lambsquarters, and yellow sweetclover ( Melilotus officinalis ) in Nebraska (Knezevic et al, 2009). Hausman et al (2013) also reported that PRE‐applied metribuzin and flumioxazin alone provided 92% waterhemp control at 60 DAPRE in soybean.…”
Section: Broadleaf Weed Controlmentioning
confidence: 99%
“…Weed management decisions must address the primary premise of herbicide use, which is to protect the crop from losses attributable to weed interference, and include decisions refl ecting choices of tillage, herbicide application timing, types of herbicides, time of weed removal, herbicide rate, row spacing, plant population density, and other factors (Beyers et al, 2002;Cox et al, 2006;Culpepper et al, 2000;Dalley et al, 2004a, b;Knezevic et al, 2002Knezevic et al, , 2003Knezevic et al, , 2009Wait et al, 1999). Weed management decisions must address the primary premise of herbicide use, which is to protect the crop from losses attributable to weed interference, and include decisions refl ecting choices of tillage, herbicide application timing, types of herbicides, time of weed removal, herbicide rate, row spacing, plant population density, and other factors (Beyers et al, 2002;Cox et al, 2006;Culpepper et al, 2000;Dalley et al, 2004a, b;Knezevic et al, 2002Knezevic et al, , 2003Knezevic et al, , 2009Wait et al, 1999).…”
mentioning
confidence: 99%